2014
DOI: 10.1186/1471-2407-14-4
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy in breast cancer significantly reduces number of yielded lymph nodes by axillary dissection

Abstract: BackgroundNeoadjuvant chemotherapy (NC) is an established therapy in breast cancer, able to downstage positive axillary lymph nodes, but might hamper their detectibility. Even if clinical observations suggest lower lymph node yield (LNY) after NC, data are inconclusive and it is unclear whether NC dependent parameters influence detection rates by axillary lymph node dissection (ALND).MethodsWe analyzed retrospectively the LNY in 182 patients with ALND after NC and 351 patients with primary ALND. Impact of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Whether or not an adequate dissection as described by current guidelines is relevant to patients who received neoadjuvant therapy has been an ongoing source of contention. Our finding of less than 10 lymph axillary lymph nodes recovered following neoadjuvant chemotherapy is validated in other studies . However, other studies have observed no effect of neoadjuvant therapy on the number of axillary lymph nodes recovered .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Whether or not an adequate dissection as described by current guidelines is relevant to patients who received neoadjuvant therapy has been an ongoing source of contention. Our finding of less than 10 lymph axillary lymph nodes recovered following neoadjuvant chemotherapy is validated in other studies . However, other studies have observed no effect of neoadjuvant therapy on the number of axillary lymph nodes recovered .…”
Section: Discussionsupporting
confidence: 89%
“…Improved disease‐free survival has been observed in patients with at least 10 axillary nodes recovered in the ALND specimen, and thus, this number has become the foundation of the practice‐based guidelines of the American Society of Breast Surgeons . However, neoadjuvant therapies, specifically those targeting human epidermal growth factor receptor 2 (HER2) positive breast cancer, have resulted in improved pathologic complete response (pCR) and, at times, obliteration of axillary lymph nodes …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the number of retrieved and examined LNs is influenced by NCT [9,10]. In our study, most patients (92.8%) completed the preplanned eight cycles of NCT, while only three cycles of NCT were utilized in previous studies [17,18].…”
Section: Discussionmentioning
confidence: 75%
“…However, based on previous observations, NCT may change the histological environment of the axillary area and reduce the number of retrieved axillary LNs [9,10]. As a result, the ypN stage can be underestimated, thereby resulting in inadequate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al [10] described similar changes in sentinel lymph nodes with a treatment effect. Erbes et al [11] demonstrated the importance of identifying postchemotherapy fibrosis and lymphocyte depletion in lymph nodes. These false positive cases were in fact not true ‘false positive' cases, as axillary lymph node FNA was performed preoperatively and follow-up histology was performed following neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%